2022
DOI: 10.1002/ccd.30134
|View full text |Cite
|
Sign up to set email alerts
|

TAVR operator volumes, trends, and geographic variations amongst Medicare beneficiaries in the United States

Abstract: Objectives: To evaluate transcatheter aortic valve replacement (TAVR) operator procedural volumes, and describe temporal and geographic trends.Background: TAVR is the standard of care for most patients with severe symptomatic aortic stenosis. Despite an association between operator procedural volume and outcomes, nationwide TAVR operator volumes have been incompletely described.Methods: We queried the National Medicare Provider Utilization and Payment Database for transfemoral TAVRs from 2014 to 2018. Annual o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 13 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…3 It is in this context that the current report 4 for TF-TAVRs from 2014 to 2018. 4 They examined operators' TF-TAVR volumes per year, temporal trends in volumes, and geographic variation in operators' density and procedural volumes. They showed that from 2014 to 2018, there was a 54% annualized increase in TAVR volume and a 31% annual increase in the number of operators, with the mean annual operator volume of TAVR increasing to 24 procedures (from mean 12.5 in 2014).…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…3 It is in this context that the current report 4 for TF-TAVRs from 2014 to 2018. 4 They examined operators' TF-TAVR volumes per year, temporal trends in volumes, and geographic variation in operators' density and procedural volumes. They showed that from 2014 to 2018, there was a 54% annualized increase in TAVR volume and a 31% annual increase in the number of operators, with the mean annual operator volume of TAVR increasing to 24 procedures (from mean 12.5 in 2014).…”
mentioning
confidence: 98%
“…It is in this context that the current report 4 should be viewed. The investigators evaluated data from the National Medicare Provider Utilization and Payment Database (MPUPD) for TF‐TAVRs from 2014 to 2018 4 .…”
mentioning
confidence: 99%
See 3 more Smart Citations